Rebecca [videorecording (DVD)] - Hitchcock, Alfred, 1899-1980; Olivier, Laurence, 1907-1989; Fontaine, Joan, 1917-2013; Sanders, George, 1906-1972; Du Maurier, Daphne, 1907-1989 (Premiere collection, 2008)
A vacationing young lady meets, falls in love with, and marries handsome and wealthy widower Maxim de Winter. He takes his new bride home to his estate, Manderley. But the new Mrs. de Winter finds her married life donimated by the sinister, almost spectral influence of Maxim's late wife, Rebecca, who still rules from beyond the grave.